Investigation of challenges in interior and surface permanent magnet synchronous machines during integrated charging operation in electric vehicles. (2018) - Iyer, K. Lakshmi Varaha; Lai, Chunyan; Mukundan, Shruthi; Dhulipati, Himavarsha; Mukherjee, Kaushik; Kar, Narayan C.
The beneficial nature of employing power electronics and drive components in conventional electric vehicle (EV) towards level 3 charging capability has propelled research activities towards integrated charging (IC) technology. However, alternating magnetic fields produced in the air-gap by AC charging currents and the stationary nature of the rotor leads to unusual loss and magnet operating characteristics. Since the same permanent magnet synchronous motor (PMSM) will be used for both traction and IC, it is important to understand the machine's behaviour during IC to optimally design the machine for both applications. Hence, this paper exclusively investigates: 1) permanent magnet operation; 2) electrical and magnet losses; 3) temperature rise; and 4) effect of winding inductances on voltages and currents, in both surface and interior traction PMSMs employed for IC in EVs. Results obtained from investigations conducted on laboratory interior and surface PMSMs using finite element analysis and experimentation are analysed and discussed.